A Meta‐Analysis and Meta‐Regression of Incidental Second Language Word Learning from Spoken Input. Issue 4 (11th June 2018) - de Vos, Johanna F.; Schriefers, Herbert; Nivard, Michel G.; Lemhöfer, Kristin
Abstract : We meta‐analyzed the effectiveness of incidental second language word learning from spoken input. Our sample contained 105 effect sizes from 32 primary studies employing meaning‐focused word‐learning activities with 1, 964 participants with typical cognitive functioning. The random‐effects meta‐analysis yielded a mean effect size of g = 1.05, reflecting generally large vocabulary gains from spoken input in meaning‐focused activities. A meta‐regression with three substantive and two methodological predictors also revealed that adult participants outperformed children in terms of word learning and that interactive learning tasks were more effective than noninteractive ones. Furthermore, learning scores were higher when measured with recognition than with recall tests. Methodologically, the use of a no‐input control group seemed to protect against an overestimation of learning effects, evidenced by smaller effect sizes. Finally, whether a pretest–posttest design was used did not influence effect sizes. All data and the analysis script are publicly available. Open Practices: This article has been awarded an Open Data badge. All data and the analysis script are publicly accessible via the Open Science Framework athttps://osf.io/92vfw . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki .